2018
DOI: 10.3390/ijerph15112547
|View full text |Cite
|
Sign up to set email alerts
|

“In my day…”- Parents’ Views on Children’s Physical Activity and Screen Viewing in Relation to Their Own Childhood

Abstract: Physical activity and screen viewing are associated with cardio-metabolic risk factors, psychological wellbeing, and academic performance among children. Across the last generation, children’s physical activity and screen viewing behaviours have changed, coinciding with changes to the home and neighbourhood environment. This study aimed to qualitatively explore parents’ views on their 8–9-year-old child’s childhood and how this compares to experiences from their own childhood, with a specific focus on physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 66 publications
0
18
0
Order By: Relevance
“…Similarly, the results of this study showed that the parents in the no IM group perceived more dangers in streets, on footpaths and crossings, and in shops and supermarkets. A recent study [ 28 ] showed how parents reduced their children’s IM and playing outdoors because they were worried about their safety, which was also related with their level of socio-economic hardships. However, they also perceived their own childhood as being better, and they acknowledged that they should maximize their child’s independent outdoor play and limit them using screens on electronic devices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, the results of this study showed that the parents in the no IM group perceived more dangers in streets, on footpaths and crossings, and in shops and supermarkets. A recent study [ 28 ] showed how parents reduced their children’s IM and playing outdoors because they were worried about their safety, which was also related with their level of socio-economic hardships. However, they also perceived their own childhood as being better, and they acknowledged that they should maximize their child’s independent outdoor play and limit them using screens on electronic devices.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [ 26 , 27 , 28 ] have revealed some spatial, social and cultural changes that have affected the behavior of children: children spend less time playing in cities; the public space in which they can play and socialize has become smaller; the freedom with which they move about has been cut. Moreover, the following reasons all entail less outdoor play: fewer children in today’s society, the few children families have, parents’ and children’s growing safety concerns, and middle-class homes buying more indoor cultural resources [ 26 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be that girls without siblings have fewer opportunities for companion play and therefore spend more time in solitary pursuits, which are often sedentary. A recent qualitative study found that parents restrict their children’s independent mobility and outdoor play due to concerns about safety [38], and so it may be that girls without siblings have more restrictions on their outdoor play on weekends. However, the associations between the number of siblings and girls’ physical activity in the present study were only very small.…”
Section: Discussionmentioning
confidence: 99%
“…Research exploring the developmental histories of elite and non-elite athletes (e.g., Baker et al, 2003 ; Côté et al, 2005 ; Gulbin et al, 2010 ), as well as more anecdotal descriptions of free-play, diversification and development (as evidenced in the development of elite Brazilian footballers; Ford et al, 2012 ), is purported to offer clues to best practise, generating “evidence-based” practises which can be adopted and applied by sports and organisations in the pursuit of excellence. However, western society has changed, and children are unable to acquire the same amount of outdoor free-play than that of previous generations (Solomon-Moore et al, 2018 ). This descriptive focus also fails to appreciate that talent development is a biopsychosocial issue and optimum solutions will be contextualised based on the interaction between physical and mechanical attributes (the “bio”), psycho-behavioural characteristics (the “psycho”), and the sociocultural environment/milieu in which the individual exists (the “social”) (Collins and MacNamara, 2019 ).…”
Section: Optimising Early Engagement In a Specialised Pathwaymentioning
confidence: 99%